Pelayanan Sosial Bagi Korban Penyalahguna Napza Di Institusi Penerima Wajib Lapor (IPWL) YP2MP (Yayasan Pendampingan Dan Pemberdayaan Masyarakat Papua Dan Papua Barat) Kota Jayapura - Patty, Rukmana; Lobo, Albertina Nasri (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2025)
The circulation of drugs (Narcotics, Psychotropic and Addictive Substances) in Indonesia is quite high. Jayapura City, which is the capital of Papua province, is one of the areas that has included an emergency level with a very alarming level of use and circulation, the majority of dealers get marijuana from Papua New Guinea which borders Jayapura City. In addition, the rise of alcohol among Papuan people who are consumed not only adults but also children. The stages of this research begin with the stages of field observation, interviews and documentation studies at the YP2MP institution. The data obtained is then analyzed descriptively using a qualitative approach, YP2MP social institutions in Jayapura City which are engaged in social rehabilitation services for Nazpa users provide services in three areas, namely Jayapura city, Jayapura district and Keerom district, including services inside and outside the institution in assisting victims of drug abusers so that they are able to recover and function socially.